Prevalence and antibiotic susceptibility pattern of e. Coli isolates from clinical samples of gulbarga city, India - SIDDARTH.B.SURWONSE; KELAMANI CHANDRAKANTH R (International Journal of Pharma and Bio Sciences, 2017)
The misuse and overuse of antibiotics has led to the selection of new strains of bacteria that resist to antibiotics, a situation which is found in the case of Escherichia coli strains. There are many types of E. coli and most of them are harmless. But some stereotypes can cause food poisoning, bloody diarrhoea and gastrointestinal infections. E. coli is the most common cause of urinary tract infections (UTIs) in humans and leading cause of enteric infections. Some of the strain can also cause kidney failure, which can lead to death. In this study we have evaluated the ability of E. coli strains to resist antibiotics isolated from infections of the gastrointestinal system and diarrhoea. The objective of this study was to determine the sensitivity of E. coli to antimicrobial drugs. A total of 285 strains of E. coli were evaluated for their antibiotic resistant pattern against eight selected antibiotics. The antibiotic sensitivity test was performed using the disc diffusion method prepared according to the standards of the Clinical and Laboratory Standard Institute (CLSI). The results showed over 53.33% of the strains were resistant to ampicillin and 69.47% were resistant to Ciprofloxacin and most of the strains were sensitive to Chloromphenicol (92.98%), Amikacin (76.49%) and Nalidixic acid (70.53%).